2019
DOI: 10.31296/aop.v3i5.112
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations among Emotional Development, Over-excitabilities and Personal Maladjustment

Abstract: This article presents a self-report inventory, the “Emotion Scale”, conducted on the basis of Dabrowski’s theory (1964) to understand the emotional development of the gifted. Two subscales, “Emotional Functions” and “Emotional Cognition” were included with 26 items. The coefficients of internal consistency (Cronbach α =.769), stability(.657~.769) and the expert validity(.714~1.000) were well reported. The formal study included 123 mathematically gifted students and 132 regular students from senior high schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In Korea, a cross-sectional study was conducted to examine the relationship between social-emotional development, gender, age, temperament, and maternal parenting behaviors [61]. Consistent with most studies, this study found that caregivers evaluated boys as having more externalizing behavior problems than girls.…”
Section: Theme 1: Social-emotional (Overall)supporting
confidence: 71%
See 2 more Smart Citations
“…In Korea, a cross-sectional study was conducted to examine the relationship between social-emotional development, gender, age, temperament, and maternal parenting behaviors [61]. Consistent with most studies, this study found that caregivers evaluated boys as having more externalizing behavior problems than girls.…”
Section: Theme 1: Social-emotional (Overall)supporting
confidence: 71%
“…Culture can affect parenting beliefs, values, and practices in raising children in a particular context [91]. A few studies (n = 10, 22%) in this review reported cultural differences in social-emotional development [25,45,46,52,[61][62][63]65,70]. One study reported significant cultural differences in how children perceived social competence between Eastern and Western cultures [62].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, it has been suggested that they are typically overexcited (Dabrowski, 1964) and oversensitive (Mendaglio, 1995) and, therefore, more emotionally involved in their activities than their peers. Reference to the construct of overexcitability has been criticized (Vuyk et al, 2016), but it continues to influence opinions in the field of giftedness, not only of families and practitioners but also of researchers (e.g., Ackerman, 1997;Chang & Kuo, 2019). Gaesser (2018) argued that there are many anxiety-inducing stressors in the everyday experience of gifted individuals (see also Cross & Cross, 2015;C.…”
Section: Emotional Response To Testing In Gifted and Highly Gifted Ch...mentioning
confidence: 99%
“…For example, it has been suggested that they are typically overexcited (Dabrowski, 1964) and oversensitive (Mendaglio, 1995) and, therefore, more emotionally involved in their activities than their peers. Reference to the construct of overexcitability has been criticized (Vuyk et al, 2016), but it continues to influence opinions in the field of giftedness, not only of families and practitioners but also of researchers (e.g., Ackerman, 1997;Chang & Kuo, 2019). Gaesser (2018) argued that there are many anxiety-inducing stressors in the everyday experience of gifted individuals (see also Cross & Cross, 2015;C.…”
mentioning
confidence: 99%